Simulated annealing to handle energy and ancillary services jointmanagement considering electric vehicles - Sousa, Tiago (2016)
The massive use of distributed generation and electric vehicles will lead to a more complex managementof the power system, requiring new approaches to be used in the optimal resource scheduling field.Electric vehicles with vehicle-to-grid capability can be useful for the aggregator players in the mitigationof renewable sources intermittency and in the ancillary services procurement. In this paper, an energyand ancillary services joint management model is proposed. A simulated annealing approach is used tosolve the joint management for the following day, considering the minimization of the aggregator totaloperation costs. The case study considers a distribution network with 33-bus, 66 distributed generationand 2000 electric vehicles. The proposed simulated annealing is matched with a deterministic approachallowing an effective and efficient comparison. The simulated annealing presents a solution closer to theone obtained in the deterministic approach (1.03% error), yet representing 0.06% of the deterministicapproach CPU time performance.